Dolichospermum lemmermannii (Cyanobacteria): a temperate species in a neotropical, eutrophic reservoir - Palacio, Hilda María (2015)
Between September 2011 and October 2012, 13 samplings at 8 stations in the Riogrande II Reservoir (Colombia) were undertaken. It is located in a high-mountainous tropical (75°32’30’’ W - 75°26’10’’ W and 6°33’50’’ N - 6o28’07’’N), which supplies water to a plant treatment for public supply and to a small hydroelectric plant. The basins of the two main tributaries of the reservoir are highly impacted by human activity. We report the presence of a Dolichospermum lemmermannii, which up to now has only been registered as a temperate and high latitude species. Also the general ecology of the species is established, such as, generation and renewal times, spatial and temporal patterns, and interaction with more important environmental variables.